2022
DOI: 10.14309/ctg.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Albumin Infusions Do Not Improve Systemic Inflammation or Cardiovascular Function in Decompensated Cirrhosis

Abstract: INTRODUCTION:Albumin is recommended in decompensated cirrhosis, and studies have shown potential immunomodulatory effects. However, 2 large trials of repeated albumin infusions demonstrated contrasting results between outpatients and hospitalized patients. We investigated markers of systemic inflammation, immune function, albumin binding, and cardiovascular function using samples from Albumin To prevenT Infection in chronic liveR failurE (ATTIRE) taken at baseline, day 5, and day 10 of the trial to identify wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Data were taken from our published dataset in which 142 patients' samples (n = 71 in targeted HAS arm, n = 71 in standard of care arm) were blindly analysed. 23 All patients selected were enrolled in the trial for at least 5 days. For this paper we divided patients into those taking NSBBs (n = 23) or not (n = 119) at baseline but did not subdivide into treatment groups as samples were taken at study recruitment prior to albumin treatment.…”
Section: Validation Of Infection Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Data were taken from our published dataset in which 142 patients' samples (n = 71 in targeted HAS arm, n = 71 in standard of care arm) were blindly analysed. 23 All patients selected were enrolled in the trial for at least 5 days. For this paper we divided patients into those taking NSBBs (n = 23) or not (n = 119) at baseline but did not subdivide into treatment groups as samples were taken at study recruitment prior to albumin treatment.…”
Section: Validation Of Infection Diagnosismentioning
confidence: 99%
“…We did not examine the plasma inflammatory markers after baseline in view of the potential confounding effect of targeted albumin therapy, 24 although we previously found no effect of albumin on these overall. 23 LBP, sCD14, TNF, IL-6, IL-8 and PCT evaluation was undertaken via Luminex assay (R&D Systems, Minneapolis, MN) according to the manufacturer's instructionssee Supplementary material and Supplementary Table 1 for details.…”
Section: Validation Of Infection Diagnosismentioning
confidence: 99%
“…On the other hand, however, there are studies that suggest that the effect of albumin may not be so strong. A recent clinical study revealed that targeted albumin infusion did not attenuate systemic inflammation or improve cardiac function in patients with decompensated cirrhosis (139). Another trial suggested that infusing albumin to normal levels in patients with advanced liver disease may not provide additional benefit (13).…”
Section: Therapeutic Effects Of Albumin In Different Clinical Pathwaysmentioning
confidence: 99%
“…An in vitro study revealed that the augmentation of serum albumin above 30 g/L was associated with the reversibility of plasma-mediated immune dysfunction by binding and inactivation PGE 2 (China et al, 2018). Intravenous albumin had however no effect on systemic inflammation, albumin function, cardiovascular mediators and biomarkers compared with standard of care in hospitalized decompensated cirrhosis (China et al, 2022). To date, the standard of care remains the treatment with albumin in addition to appropriate antibiotics in SBP (Bajaj et al, 2021) as well as in acute kidney injury.…”
Section: Therapeutic Modulation Of Monocyte and Macrophage Function I...mentioning
confidence: 99%